Effect of a virtually supervised fitness program on physical fitness and perceived stress in university teachers during lockdown by COVID-19 - Manito Quintero, Alejandro; Barranco Ruiz, Yaira (SPORT TK-EuroAmerican Journal of Sport Sciences, 2022)
The objective of this study was to analyze the effect of a virtually supervised fitness program on physical fitness and perceived stress in university teachers during lockdown due to COVID-19. A total of 15 university teachers participated in a virtual fitness program based on new fitness trends (4-weeks / 2-days / week / 45-minutes / session) during COVID-19 lockdown. Perceived physical fitness using the International-Fitness-Scale (IFiS) and perceived stress using the Perceived-Stress-Questionnaire (PSQ-30) were evaluated pre and post intervention. The virtual fitness program significantly improved the perception of general physical fitness (p = 0.011) and muscle strength (p = 0.024), and generated a significant decrease in the perception of stress (p <0.001). A virtually supervised fitness program based on the “whole-body HIIT” fitness trend could be an effective strategy to ensure healthy levels of physical fitness and stress in university teachers during confinement situations.